H.I.V.E. : dreadnought / 4. - Walden, Mark (H.I.V.E, 2011)
When one of the world's most powerful villain's threatens a global Armageddon and names himself head of a sinister new world order, Otto, Wing, and the other students at H.I.V.E. must abort their training exercise in the Arctic to battle the madman and save themselves and the world.